A validated direct spectrofluorimetric method for quantification of mirtazapine in human whole blood. Issue 6 (2010) - Saini, Balraj; Kaushal, Manjula; Bansal, Gulshan
Abstract : A spectrofluorimetric method for estimation of mirtazapine in human whole blood was developed and validated. The recovery efficiency of the processing method was 95–98%. The analytical method was linear over drug concentration of 10–200 ng/ml. The limit of quantification was 10 ng/ml. The method was precise with %RSD for intra-day and inter-day precision being <3.0 and 1.5, respectively. Excellent recoveries (97.87–99.69%) were achieved during accuracy studies. The method was robust to small changes in processing method and instrumental parameters. The present method can be employed for direct fluorimetric determination of mirtazapine in human whole blood during clinical studies.